(untitled) (World Bulletin of Public Health, 2025)
Class III malocclusion represents one of the most complex and clinically significant forms of dentofacial anomalies, characterized by disrupted occlusal relationships in which the lower jaw occupies a more anterior position relative to the upper jaw. This pathology is among the most common orthodontic problems encountered in various age groups and requires a comprehensive interdisciplinary approach to diagnosis and treatment.